Combined effect of Tetracycline compounds and essential oils on antimicrobial resistant Salmonella enterica isolated from the swine food chain - Maggio, Francesca; Lauteri, Carlotta; Rossi, Chiara; Ferri, Gianluigi; Serio, Annalisa; Vergara, Alberto; Paparella, Antonello (Frontiers in Microbiology, 2024)
Antimicrobial resistance (AMR) poses risks for food stakeholders because of the spread of resistant microbes and potential foodborne diseases. In example, pigs may carry Salmonella strains, which can infect humans through contaminated food preparations. Due to their antibacterial properties and capacity to modulate bacterial drug resistance, essential oils (EOs) are attracting interest as prospective substitutes for synthetic antimicrobials which can help to reverse microbial resistance. Hence, the present study evaluates the antimicrobial effectiveness of the combination of tetracycline (Tc) compounds and Coridothymus capitatus (CC), Thymus capitatus L. (TC), and Thymus serpyllum (TS) EOs on 11 tetracycline-resistant Salmonella enterica strains isolated from the swine food chain. The kind of interaction between Tc and EOs was evaluated by Fractional Inhibitory Concentration Index (FICI), while the composition of the EOs phytocomplex was linked to Tc antibacterial activity by Principal Component Analysis (PCA). Interestingly, the EOs increased the strains susceptibility to Tc, inhibiting their growth despite the antimicrobial resistance. In most cases, synergistic and commutative effects were detected, as the combination of EOs and Tc compounds resulted in a noticeable decrease in the concentration (from 256 to 4 μg/mL) necessary to inhibit the strains. Thymol, carvacrol, linalool, sabinene, and other EO terpenoid components were revealed as the molecules working in concert with the Tc drug to increase the susceptibility of S. enterica strains to the treatment. Comprehending which molecules of the EOs phytocomplex, beside the main compounds, affect bacterial inhibition, might help to develop a tailor-made approach related to counteract the resistance of specific strains to different antibiotics.